Divergent host plant preference causes assortative mating between sympatric host races of the ladybird beetle, Henosepilachna diekei. (24th September 2013) - Matsubayashi, Kei W.; Kahono, Sih; Katakura, Haruo
<x xml:space="preserve">Abstract</x> Divergent host preference (i.e. host fidelity) plays a significant role in the speciation process in phytophagous insects. However, how and to what extent this divergence reduces gene flow between populations has rarely been measured. Here, we estimated the intensity of assortative mating caused solely by host fidelity in two host races of the phytophagous ladybird beetle Henosepilachna diekei, specialized on Mikania micrantha (Asteraceae) and Leucas lavandulifolia (Lamiaceae) in West Java, Indonesia. These host races mated randomly in the absence of host plants under laboratory conditions, but demonstrated nearly complete assortative mating in field cages with the two host plants, by spending almost all of their time on their respective host plants. The frequency of assortative mating in the field cages was not affected drastically by host plant patch structure. These results suggest that fidelity to the different host plants yields directly almost complete reproductive isolation between the host races by limiting the habitat on the respective host plant. In addition, the high host fidelity also ensures female oviposition on the original host plant. As larvae cannot survive on non‐host plants, a positive association between female oviposition preference and larval performance on the host plant on which the beetles are specialized will further facilitate the evolution of host fidelity. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 606–614.